The Effect of Career Development and Wellbeing Programs on Employee Retention in Manufacturing Companies - Khoirunnisa, Zalpa; Aisyah, Aprilia Dwi (Talent: Journal of Economics and Business, 2024)
Employee retention is an important issue for manufacturing companies, especially in the face of a shortage of qualified workers. The company's ability to retain potential employees is crucial, because retaining competent employees is more effective than looking for new employees. Career development and employee well-being programs are considered important factors in increasing loyalty and job satisfaction, which in turn can reduce employee turnover rates. This study aims to examine the influence of career development and welfare programs on employee retention in manufacturing companies. The research method used was qualitative with a purposive sampling approach, involving 60 respondents who worked for more than two years. The variables studied included career development (dedication, commitment, passion, and learning) as well as welfare programs (salary, supervision, co-workers, and communication), which were associated with employee retention (working conditions, vision and mission, work attitudes, and work assessments). The results of the study show that clear career development and supportive wellbeing programs significantly increase employee commitment, loyalty, and retention. The practical implications of these findings are the importance of companies offering appropriate career development opportunities and adequate wellbeing programs to create a productive work environment and high employee loyalty.